Emerging challenges of an urban creative economy: reflections on the governance of creative clusters in Taipei City. Issue 2 (1st February 2018) - Lin, Cheng-Yi
ABSTRACT: Retaining the global mobile creative class has been considered a crucial strategy for driving creative economic development in inner cities. However, implementing the global creative city strategy overemphasizes the significance of amenity-based creative economic landscapes over institutional collaborations in contributing to the situated governance dynamics of creative clusters. Drawing on insights from an evolutionary perspective, this paper scrutinizes the extent to which creative city strategies foster the situated development of creative clusters based on a case study of Taipei. The paper argues that developing the urban creative economy requires a context-specific understanding of the urbanization process, and should involve an institutional collaboration to articulate the socio-spatial co-evolution between the diversified dynamics of creative clusters and urban form. This paper advocates reflexive thinking on neoliberal city strategies to develop a conjunctive, diverse and substantial creative policy to support alternative paths of creative city development.